Norway : Staff Report for the 2000 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2001)
Norway, one of the world's richest economies and the second largest oil exporter, has been a model of prudent economic management of resource wealth. Executive Directors commended the impressive economic performance, marked by sustained solid growth, low inflation, unemployment, and strong fiscal and external positions. They noted that countercyclical fiscal management was a key pillar of the strategy, and stressed the need to tighten fiscal and monetary policies, accelerate structural reforms, increase labor supply, restrain public expenditure, and move forward with privatization initiatives.